2021
DOI: 10.1016/j.jcot.2020.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral total knee arthroplasty: Simultaneous versus staging in the same or in twice hospitalization

Abstract: Background and objective: Arthroplasty is the main treatment in patients with advanced knee osteoarthritis. In bilateral lesions, it is frequently performed in two simultaneous or separate surgical procedures. In this regard, the present study aimed to compare the results of knee arthroplasty in two joints simultaneously at two different times. Method: In general, all 40e70 years old patients in need of complete bilateral total knee arthroplasty (BTKA) were enrolled in this descriptive cross-sectional study du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…BUN: Blood urea nitrogen; ASA: American Society of Anesthesiologists. function and relieve pain (1)(2)(3)(4)(5)(6)(7)(19)(20)(21)(22). In recent years, the nomogram is a widely used prediction tool in the field of clinical medicine, which has the ability to predict the occurrence risk of adverse events individually.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…BUN: Blood urea nitrogen; ASA: American Society of Anesthesiologists. function and relieve pain (1)(2)(3)(4)(5)(6)(7)(19)(20)(21)(22). In recent years, the nomogram is a widely used prediction tool in the field of clinical medicine, which has the ability to predict the occurrence risk of adverse events individually.…”
Section: Figurementioning
confidence: 99%
“…Studies have found that after SBTKA, the infection rate and length of hospital stay of patients are reduced, but the incidence of 90-day mortality, venous thromboembolism and neurological complications is increased (4). In addition, the risk of pulmonary embolism, cerebral embolism (5), blood transfusion rate (6,7), cardiac complications, urinary retention, and deep infection are significantly increased (8). At present, the comparative studies after SBTKA and staged bilateral TKA are relatively common, and many studies have provided a comprehensive assessment of complication incidence, clinical efficacy and mortality after SBTKA (4,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Consecutive procedures virtually double the surgery and anesthesia times, and such doubling has consequences. Furthermore, some authors used spinal anesthesia, 5 whereas others preferred epidural 7 or general anesthesia; 6 some used a pneumatic tourniquet, 6,7 and others did not. 5 The technique of TKA with two surgical teams working simultaneously allows the performance of both procedures in the time equivalent to one surgery and under the same amount of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that after SBTKA, the infection rate and length of hospital stay of patients are reduced, but the incidence of 90-day mortality, venous thromboembolism and neurological complications is increased [4].In addition, the risk of pulmonary embolism, cerebral embolism [5], blood transfusion rate [6,7], cardiac complications, urinary retention, and deep infection are signi cantly increased [8].At present, the comparative studies after SBTKA and staged bilateral TKA are relatively common, and many studies have provided a comprehensive assessment of complication incidence, clinical e cacy and mortality after SBTKA [4,[8][9][10].Due to the lack of established indications for SBTKA, it is always controversial to determine the age of patients, and previous studies only con rmed that patients aged 75 and above are generally not recommended to undergo SBTKA [11][12][13].Recent studies by scholars [14] also only con rmed that patients under 75 years of age and ASA1 grade or grade 2 received SBTKA, and the incidence of complications was no different from that of unilateral TKA.Regrettably, these studies did not provide further studies on the incidence of complications at various ages of SBTKA and the selection of the optimal age.For complications after TKA, some scholars used the nomograms prediction model to predict the probability of complications within 30 days after primary TKA [15].Since the incidence of complications after bilateral TKA increased signi cantly during the same period, it was necessary to establish a nomogram prediction model for complications after SBTKA and identify high-risk patients as early as possible in order to reduce the risk of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%